Organic silicon marine antifouling paint imitating mussel adhesion

By introducing dopamine-modified structure into the polysiloxane molecules and combining the molecular structural characteristics of the mussel bonded silk, a dopamine-modified polysiloxane polymer with high bonding strength is formed, which solves the problem of poor bonding in traditional marine antifouling coatings, and achieves both high bonding and low surface energy antifouling effects.

CN119529667APending Publication Date: 2025-02-28CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411683061.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The toxic components in traditional marine antifouling coatings cause harm to the marine environment, and the low mechanical strength and poor adhesion of polysiloxane coatings in the marine environment lead to a decrease in the antifouling effect.

Method used

By introducing dopamine-modified structure into the polysiloxane molecule, combining the molecular structural characteristics of the mussel bonded silk, a dopamine-modified polysiloxane polymer with high bonding power is formed, and blended with the hydrophobic polysiloxane polymer, the excellent bonding and anti-fouling effect of the coating is achieved.

Benefits of technology

It achieves the effect of maintaining low surface energy and anti-fouling effect, significantly improving the adhesion of the coating, enhancing the stability and service life of the anti-fouling coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148839840000031
    Figure BDA0005148839840000031
  • Figure BDA0005148839840000032
    Figure BDA0005148839840000032
  • Figure BDA0005148839840000061
    Figure BDA0005148839840000061
Patent Text Reader

Abstract

The invention discloses a mussel bonding imitating organosilicone marine antifouling paint, which is characterized in that catechol group modified polysiloxane resin is synthesized on the basis of an effective component catechol group bonded by mussels, and then the organosilicone marine antifouling paint with firm bonding performance and low surface energy performance is prepared. Firstly, a modified polysiloxane precursor is synthesized through a reversible addition-fragmentation chain transfer polymerization reaction, and then grafting of catechol groups on target polysiloxane resin is achieved through an ammonolysis reaction of a dopamine polymer, so that the polymerization inhibition effect of phenol groups is overcome, and synthesis of a target polymer is achieved. The coating can be applied to antifouling of marine facilities, and is particularly suitable for various marine facilities immersed in a seawater environment for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of marine antifouling coating technology and underwater coating protection technology, and particularly relates to a functional modified fouling-releasing marine antifouling coating. Background Art

[0002] Traditional marine antifouling coatings mainly rely on heavy metal oxides, such as copper oxide, or organic tin compounds (such as tributyltin, TBT) as active ingredients. This type of antifouling coating inhibits or kills attached organisms through the release of heavy metal ions or toxic substances. However, many toxic ingredients in traditional antifouling coatings are highly destructive to marine life and the ecological environment, and will gradually accumulate in the ocean to produce ecotoxicity. Compounds such as tributyltin have long been proven to cause serious ecological harm to the marine environment, so all countries have enacted laws to prohibit or restrict their use. Therefore, it is urgent to find non-toxic and environmentally friendly antifouling coatings.

[0003] Driven by environmental protection requirements, fouling-releasing marine antifouling coatings based on polysiloxane have gradually become a research hotspot in recent years. Polysiloxane is a polymer material based on silicon-oxygen bonds. It has excellent corrosion resistance, low surface energy, good thermal stability, and is not easy to degrade. It shows good stability in the marine environment. Antifouling coatings based on polysiloxane mainly use their low surface energy to prevent biological attachment, and reduce the adhesion strength through a smooth surface structure, making it easier for biological fouling to fall off under the impact of water flow, thereby achieving the effect of fouling release. This type of coating is non-toxic and environmentally friendly, avoiding the impact of toxic components of traditional antifouling coatings on the marine environment. It is an environmentally friendly marine antifouling material that meets the needs of sustainable development.

[0004] The main advantage of polysiloxane fouling release antifouling coatings is that they achieve antifouling effects through physical methods and do not rely on the release of chemical toxins. This not only reduces the risk of environmental pollution, but also significantly improves the application life of the material. Polysiloxane has a low surface energy, and underwater attached organisms are not easy to firmly adhere to its surface, and are easy to fall off under high-speed water flow. Unlike traditional toxic antifouling coatings, the working principle of polysiloxane antifouling coatings is physical obstruction and self-cleaning, that is, by reducing the adhesion of fouling and removing fouling with the help of fluid shear force. Although polysiloxane fouling release antifouling coatings have significant environmental protection and antifouling effects, they also face some challenges during application. First, the polysiloxane matrix usually exhibits the disadvantage of low mechanical strength, especially in harsh marine environments, which is easily damaged, affecting its antifouling effect. Secondly, the adhesion of polysiloxane materials is poor, especially in high-velocity water environments, the coating may fall off or crack, resulting in a decrease in antifouling effect and the need for frequent maintenance and repair.

[0005] Poor adhesion is an important problem of polysiloxane fouling-release antifouling coatings. Although the low surface energy brought by the silicon-oxygen bond structure between polysiloxane matrix molecules helps to reduce biological attachment, it also weakens the bonding force between the coating and the substrate. This defect is particularly prominent in marine applications because the marine environment has complex physical and chemical conditions, such as salt spray, ultraviolet radiation, tidal changes, and seawater scouring, which all place high demands on the adhesion of the coating. In addition, due to the poor flexibility of polysiloxane, it is easy to crack on the surface of the substrate, further reducing the bonding effect. Therefore, how to significantly improve the adhesion of polysiloxane antifouling coatings while maintaining excellent antifouling performance is a major problem in current research and application.

[0006] In order to solve this problem, some current studies have attempted to enhance the adhesion between the polysiloxane matrix and the substrate by chemical bonding. For example, by introducing functional groups that can form chemical bonds with the substrate into the polysiloxane molecular structure, or using surfactants to improve the interfacial affinity between the coating and the substrate. In addition, copolymerizing or compounding polysiloxane with other polymer materials such as polyurethane and epoxy resin is also an improvement approach, the purpose of which is to optimize the elastic modulus of the coating to adapt to the complex marine environment. However, these modification measures often affect the low surface energy characteristics of polysiloxane, so various properties need to be weighed in practical applications. Summary of the invention

[0007] Due to the material characteristics of the polymer molecular structure, the conventional fouling-release polysiloxane marine antifouling coating has poor adhesion to the substrate or intermediate paint, and faces problems such as easy falling off and low stability in use during actual service. Therefore, it is necessary to improve its adhesion performance without affecting the antifouling effect of such coating (antifouling is achieved by utilizing the low surface energy characteristics). The object of the present invention is to provide a silicone marine antifouling coating imitating mussel adhesion, combining the molecular structure characteristics of dopamine, the main secretion of mussel adhesive silk, to graft the catechol structural group into the non-polar siloxane structure, so as to utilize the catechol structure to achieve a firm adhesion with the substrate or intermediate paint. The difference in molecular polarity and molecular flexibility of dopamine-modified polysiloxane polymer and hydrophobic polysiloxane polymer is utilized to achieve phase separation of the polymer, and the hydrophobic siloxy structure (from the hydrophobic polysiloxane polymer molecule) is exposed on the coating surface, ensuring that the coating has excellent low surface energy characteristics. The adhesive catechol structure (derived from the dopamine-modified polysiloxane polymer) is enriched at the contact surface between the coating and the substrate or the intermediate paint. Finally, the contact interface between the cured coating and the substrate or the intermediate paint maintains excellent bonding effect, while the coating surface maintains excellent low surface energy characteristics, thereby having an excellent anti-fouling effect.

[0008] The present invention is implemented by the following technical solutions:

[0009] In a first aspect, the present invention provides a mussel-resistant organic silicon marine antifouling coating, which comprises, by weight: (1) 15 to 30 parts of component A; (2) 4 to 8 parts of component B; (3) 0.5 to 1 part of component C;

[0010] in,

[0011] Component A includes by weight:

[0012]

[0013] Component B includes by weight:

[0014]

[0015] The dopamine-modified polysiloxane polymer is prepared by free radical copolymerization and aminolysis reaction in sequence, and the specific steps are as follows:

[0016] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent are added in sequence, and then the temperature is raised to 65-75° C. for reaction for 5-8 hours;

[0017] (2) pouring the reaction product into 5° C. methanol and filtering it multiple times, and drying the filtered product under vacuum conditions to obtain a prepolymer;

[0018] (3) Add the prepolymer into a reaction kettle protected by argon, then add the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir and react for 20 to 26 hours at room temperature;

[0019] (4) The product after the reaction was precipitated into an excess of 0.5 wt % aqueous hydrogen chloride solution, and the polymer was recovered by filtration, followed by precipitation purification using a large amount of deionized water, and finally the purified polymer was dried and collected under vacuum conditions.

[0020] Preferably, the unsaturated pentafluorophenol ester monomer is selected from one of pentafluorophenyl acrylate, pentafluorophenyl methacrylate and 4-vinylphenyl pentafluorobenzoate.

[0021] Preferably, the unsaturated MQ type silicone resin is selected from methyl vinyl MQ type siloxane resin, and its M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C.

[0022] Preferably, the unsaturated acrylic acid ester monomer is selected from butyl methacrylate, lauric methacrylate and butyl acrylate.

[0023] Preferably, the chain transfer agent is a RAFT agent, specifically one selected from 2-(dodecylthiocarbonylthio)-2-methylpropionic acid, 2-cyano-2-propyl dodecyl trithiocarbonate, cyanomethyl dodecyl trithiocarbonate, and 2-(dodecylthiocarbonylthiothio)propionic acid.

[0024] Preferably, the solvent is selected from toluene, butyronitrile and acetone.

[0025] Preferably, the weight ratio of the unsaturated pentafluorophenol ester monomer, the unsaturated MQ type silicone resin, the unsaturated acrylate monomer, the chain transfer agent, the initiator azobisisobutyronitrile, and the solvent is 2: (30-45): (5-10): (0.1-0.4): (0.5-1): (40-80).

[0026] Preferably, the dopamine salt monomer is selected from one of 6-hydroxydopamine hydrochloride, dopamine hydrochloride and 5-hydroxydopamine hydrochloride.

[0027] Preferably, the weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer and triethylamine is (30-50): (50-120): (3-5): (5-10).

[0028] Preferably, the hydroxyl-terminated polysiloxane resin is selected from α,ω-dihydroxypolydimethylsiloxane having a viscosity of 2800-10000 mPa·s at 25°C.

[0029] Preferably, the auxiliary agent is selected from at least one of a wetting and dispersing agent, a defoaming agent and a leveling agent.

[0030] Specifically, the wetting and dispersing agent is selected from BYK116, BYK169 of BYK Company, and 901, 903 of Deqian Company.

[0031] Specifically, the defoaming agent is selected from BYK065, BYK066N of BYK Company, and EFKA2020 of Efka of the Netherlands.

[0032] Specifically, the leveling agent is selected from one of German BYK308, BYK310 and BYK373.

[0033] Preferably, the pigment filler is common in the field, and there is no special requirement. As a preferred embodiment, it is selected from but not limited to one of calcium carbonate, ferric oxide, titanium dioxide, barium sulfate, kaolin, and zinc oxide.

[0034] Preferably, the first solvent is selected from one of methanol, xylene and acetone.

[0035] Preferably, the curing agent is selected from one of tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(isomethacryloyloxy)propyltrimethoxysilane and γ-methacryloyloxypropyltriisopropoxysilane.

[0036] Preferably, the second solvent is selected from one of acetone, butanone and acetylacetone.

[0037] Preferably, the catalyst is selected from dibutyltin diosilicate, stannous octoate, and organic bismuth.

[0038] Preferably, the third solvent is selected from one of acetylacetone, cyclohexanone and toluene.

[0039] In a second aspect, the present invention provides a method for preparing the mussel-bonded organosilicon marine antifouling coating described in the first aspect, which can be prepared in a conventional manner. First, component A, component B, and component C are prepared separately and sealed and stored, specifically comprising the following steps:

[0040] (1) Adding a hydroxyl-terminated polysiloxane resin, a dopamine-modified polysiloxane polymer, an auxiliary agent, and 50% of the first solvent to a dispersing and stirring device in sequence, and then dispersing at 100 rpm for 20 min, then adding a pigment and a filler and 50% of the first solvent to the dispersing and stirring device, and continuing to disperse at the same speed for 20 min, i.e., preparing component A, and then sealing and storing;

[0041] (2) using a dispersing and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;

[0042] (3) Using a dispersing and stirring device at 50 rpm, the catalyst and the third solvent are dispersed for 10 minutes to prepare component C, which is then sealed and stored.

[0043] In the third aspect, the present invention also provides a coating prepared by the mussel-bonded silicone marine antifouling coating described in the first aspect, wherein component A, component B, and component C are evenly mixed using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc., and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. Although methylvinyl MQ silicone resin has unsaturated groups, since the groups are directly connected to the silicon-oxygen network, they have large steric hindrance and are difficult to approach and effectively polymerize during free radical polymerization. However, the introduction of a type of highly reactive nitrogen gas into unsaturated pentafluorophenol ester monomers can form stable free radical intermediates. When methylvinyl MQ silicone resin, unsaturated pentafluorophenol ester monomers, and unsaturated acrylate monomers are subjected to free radical polymerization together, an "alternating" effect of free radical copolymerization can be produced, that is, the stable free radicals produced by the unsaturated pentafluorophenol ester monomers and the unsaturated acrylate monomers can be effectively guided to the unsaturated structure of the methylvinyl MQ silicone resin, and a stable copolymer product can be formed, overcoming the disadvantage that methylvinyl MQ silicone resin alone is difficult to undergo free radical polymerization.

[0046] 2. The pentafluorophenol group in the unsaturated pentafluorophenol ester monomer is highly active and may react with other free radicals or reaction intermediates during ordinary free radical polymerization, such as cross-linking or asymmetric chain growth, resulting in loss of monomer functionality. The mild conditions and low free radical concentration of RAFT polymerization help avoid side reactions, thereby retaining the reactivity and functionality of the pentafluorophenol group of pentafluorophenol acrylate. The resulting polymer can continue to be functionalized in subsequent steps to retain its specific chemical properties.

[0047] 3. Since the dopamine structure (or catechol structure) of the main component of mussel secretion is a common free radical aggregation inhibitor, it is impossible to introduce the catechol structure into the modified siloxane polymer by free radical copolymerization. However, the dopamine salt monomer can undergo an aminolysis reaction with the pentafluorophenol structure formed in the prepolymer. In an environment where an excess of amine solution exists, the pentafluorophenol structure on the prepolymer molecular chain is replaced by the catechol structure, thereby introducing the catechol structure into the polymer molecular chain to synthesize a dopamine-modified polysiloxane polymer.

[0048] 4. The finally prepared mussel-bonded silicone marine antifouling coating comprises a hydrophobic hydroxyl-terminated polysiloxane resin and a dopamine-modified polysiloxane polymer which are uniformly mixed by mechanical stirring. During the curing process, phase separation occurs due to the difference in polarity / non-polarity of the molecular structure. At the same time, the hydrophobic hydroxyl-terminated polysiloxane resin undergoes a three-dimensional crosslinking reaction to form a network structure. Thus, the dopamine-modified polysiloxane polymer can be enriched in the contact area between the coating and the substrate or the intermediate paint based on phase separation, giving full play to the advantage of the high bonding force of catechol and achieving the effects of both low surface energy antifouling and excellent bonding. DETAILED DESCRIPTION

[0049] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, without departing from the concept of the present invention, several variations and improvements can be made. These all belong to the protection scope of the present invention.

[0050] The coating of the present invention is prepared by synthesizing a dopamine-modified polysiloxane polymer and blending it with a hydrophobic hydroxyl-terminated polysiloxane resin. During the final curing process for preparing the coating, the hydrophobic hydroxyl-terminated polysiloxane resin undergoes a cross-linking reaction to generate a three-dimensional network structure, thereby constructing the main body of the cured coating. The polar dopamine-modified polysiloxane polymer can be enriched in the bonding area between the coating and the substrate or the intermediate paint through phase separation, thereby ensuring that the coating has an excellent bonding effect, while the coating surface still maintains anti-fouling advantages such as low surface energy, thereby maintaining a reliable anti-fouling effect.

[0051] The raw materials used in the examples are shown in Table 1. The specific implementation is not limited to the raw materials in Table 1, and corresponding products can be selected according to the above. Other raw materials used in the examples are all commercially available chemical reagents.

[0052] Table 1

[0053]

[0054]

[0055] Preparation of dopamine-modified polysiloxane polymer 1

[0056] The weight ratio of unsaturated pentafluorophenol ester monomer 2-1, unsaturated MQ type silicone resin 3-1, unsaturated acrylic ester monomer 4-1, chain transfer agent 5-2, initiator azobisisobutyronitrile, and solvent 6-1 is 2:35:5:0.3:1:70.

[0057] The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer 7-1, and triethylamine is 35:80:5:8.

[0058] The specific preparation process is as follows:

[0059] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 70° C. to react for 7 h;

[0060] (2) pouring the reaction product into 5° C. methanol and filtering it multiple times, and drying the filtered product under vacuum conditions to obtain a prepolymer;

[0061] (3) In a reaction kettle protected by argon, add the prepolymer, then add the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir and react at room temperature for 22 hours;

[0062] (4) The product after the reaction is precipitated into an excess of 0.5% (mass fraction) aqueous hydrogen chloride solution, and the polymer is recovered by filtration, and then a large amount of deionized water is used for precipitation purification, and finally the purified polymer is dried and collected under vacuum conditions.

[0063] Preparation of dopamine-modified polysiloxane polymer 2

[0064] The weight ratio of unsaturated pentafluorophenol ester monomer 2-2, unsaturated MQ type silicone resin 3-2, unsaturated acrylic ester monomer 4-1, chain transfer agent 5-1, initiator azobisisobutyronitrile, and solvent 6-1 is 2:30:7:0.1:0.5:40.

[0065] The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer 7-2 and triethylamine is 30:120:4:10.

[0066] The specific preparation process is as follows:

[0067] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 65° C. to react for 5 h;

[0068] (2) pouring the reaction product into 5° C. methanol and filtering it multiple times, and drying the filtered product under vacuum conditions to obtain a prepolymer;

[0069] (3) In a reaction kettle protected by argon, add the prepolymer, then add the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir and react at room temperature for 26 hours;

[0070] (4) The product after the reaction is precipitated into an excess of 0.5% (mass fraction) aqueous hydrogen chloride solution, and the polymer is recovered by filtration, and then a large amount of deionized water is used for precipitation purification, and finally the purified polymer is dried and collected under vacuum conditions.

[0071] Preparation of dopamine-modified polysiloxane polymer 3

[0072] The weight ratio of unsaturated pentafluorophenol ester monomer 2-3, unsaturated MQ type silicone resin 3-2, unsaturated acrylate monomer 4-2, chain transfer agent 5-3, initiator azobisisobutyronitrile, and solvent 6-2 is 2:45:10:0.4:0.6:80.

[0073] The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer 7-2, and triethylamine is 50:50:3:5.

[0074] The specific preparation process is as follows:

[0075] (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent were added in sequence, and then the temperature was raised to 75° C. to react for 8 h;

[0076] (2) pouring the reaction product into 5° C. methanol and filtering it multiple times, and drying the filtered product under vacuum conditions to obtain a prepolymer;

[0077] (3) In a reaction kettle protected by argon, add the prepolymer, then add the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir and react for 20 hours at room temperature;

[0078] (4) The product after the reaction is precipitated into an excess of 0.5% (mass fraction) aqueous hydrogen chloride solution, and the polymer is recovered by filtration, and then a large amount of deionized water is used for precipitation purification, and finally the purified polymer is dried and collected under vacuum conditions.

[0079] Examples 1-5

[0080] The proportions of the components A, B, and C of Examples 1-5 are shown in Table 2, and the proportions of the components of Examples 1-5 are shown in Table 3.

[0081] Table 2

[0082] Components Example 1 Example 2 Example 3 Example 4 Example 5 A 15 20 30 25 30 B 4 8 8 5 5 C 0.5 1 0.5 0.6 0.8

[0083] Table 3

[0084]

[0085]

[0086] The preparation steps of a mussel-bonded organosilicon marine antifouling coating of Examples 1-5 are as follows. In actual application, it is prepared according to the conventional method of marine antifouling coating, but is not limited to this preparation method.

[0087] (1) Adding a hydroxyl-terminated polysiloxane resin, a dopamine-modified polysiloxane polymer, an auxiliary agent, and 50% of the first solvent to a dispersing and stirring device in sequence, and then dispersing at 100 rpm for 20 min, then adding a pigment and a filler and 50% of the first solvent to the dispersing and stirring device, and continuing to disperse at the same speed for 20 min, i.e., preparing component A, and then sealing and storing;

[0088] (2) using a dispersing and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing;

[0089] (3) using a dispersing and stirring device to disperse the catalyst and the third solvent at 50 rpm for 10 min, i.e., preparing component C, and then sealing and storing;

[0090] (4) Component A, component B, and component C are mixed uniformly using conventional dispersion processes and equipment, and applied by spraying, rolling, brushing, etc. After curing for at least 48 hours, a coating with a film thickness of 150 to 250 μm is prepared.

[0091] Comparative Example 1

[0092] Compared with Example 1, no RAFT agent was added to the dopamine-modified polysiloxane polymer of Comparative Example 1 during the preparation process, and the remaining components and weight parts were the same, and the preparation process was also the same as that of Example 1.

[0093] Comparative Example 2 (Ordinary silicone low surface energy marine antifouling coating)

[0094] The common organosilicon low surface energy marine antifouling paint comprises the following raw materials in parts by weight: 90.0 parts of polysiloxane resin, 30.0 parts of pigment and filler, 4.0 parts of cross-linking curing agent, 1.5 parts of catalyst, 0.5 parts of auxiliary agent and 10.0 parts of solvent.

[0095] The polysiloxane resin is α, ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s; the pigment is zinc oxide; the cross-linking curing agent is tetraethyl orthosilicate; the catalyst is dibutyltin disilicate; the auxiliary agent is 0.5 parts of BYK161 dispersant from BYK; and the solvent is xylene.

[0096] (1) 90.0 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s and 30.0 parts of micron-sized zinc oxide were added to a disperser and dispersed at 300 rpm for 30 min. Subsequently, 0.5 parts of BYK161 dispersant from BYK was added to the disperser at 200 rpm and dispersed for 30 min. The mixture was then ground with a sand mill to a fineness of less than 40 μm to prepare a pre-dispersed slurry and canned for standby use.

[0097] (2) 4.0 parts of tetraethyl orthosilicate and 10.0 parts of xylene were mixed evenly to prepare a crosslinking curing agent component, which was then canned for standby use; 1.5 parts of dibutyltin dioxysilicate and 20.0 parts of xylene were mixed evenly to prepare a catalyst component, which was then canned for standby use;

[0098] (3) Before use, the pre-dispersed slurry, the cross-linking curing agent component, and the catalyst component are stirred uniformly according to the ratio. After the obtained coating is applied and cured, a common organic silicon low surface energy marine antifouling coating with a thickness of 150 to 200 μm is obtained.

[0099] <Specific test experiments and conditions>

[0100] Test 1: Surface Free Energy

[0101] The contact angles of deionized water and diiodomethane on the surface of the cured coating were measured using the XG-CAMC3 fully automatic contact angle meter produced by Shanghai Xuanzhun Instrument Co., Ltd. Before the measurement, the coating surface needs to be cleaned with anhydrous ethanol and dried, and then the surface free energy of the coating is calculated according to the Owens two-liquid method.

[0102] Test 2: Pull-off method for adhesion (steel plate, epoxy intermediate paint)

[0103] The adhesion of the coating applied on the corresponding substrate or epoxy intermediate paint was measured using the BGD500 digital semi-automatic adhesion tester produced by Guangzhou Biaogeda Precision Instrument Co., Ltd. The steel plate needs to be polished with 800-grit sandpaper before use, and the epoxy intermediate paint used is the epoxy micaceous iron intermediate paint produced by Shanghai Jinsi Di.

[0104] Test 3: Antifouling performance

[0105] A suspension containing at least 108 units of Streptococcus salivarius was dispersed in 20 ml of tryptic soy broth and incubated at 38°C, 5% CO2 for 2 hours. The suspension was then further diluted and inoculated in agar supplemented with 5% sheep blood and incubated at 38°C, 5% CO2 for 48 hours, and then the units containing six colonies were dispersed in 10 ml of tryptic soy broth. Subsequently, 20 ml of the above bacterial suspension was covered on the coating of 10×5 cm area and incubated at 38°C, 5% CO2 for 24 hours. After the incubation, each sample needed to be rotated and rinsed in 45 ml of distilled water for 30 seconds, and then rinsed with 50 ml of distilled water to remove non-sticky materials. The surface-adherent bacteria were observed using a Simga300 scanning electron microscope produced by Carl Zeiss, Germany.

[0106] The specific test results of Examples 1-5 and Comparative Examples 1-2 are shown in Tables 4 and 5.

[0107] Table 4

[0108]

[0109] Table 5

[0110]

[0111] The above tests confirm that the coatings of the examples and the comparative examples have lower surface free energy, thus exhibiting excellent antifouling performance. The advantage of the present invention is that the examples have excellent adhesion on various polar substrates, which is much stronger than the comparative examples, and exhibits excellent bonding effect.

[0112] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A mussel-resistant organic silicon marine antifouling coating, characterized in that: In terms of weight fraction, it comprises: (1) 15 to 30 parts of component A; (2) 4 to 8 parts of component B; (3) 0.5 to 1 part of component C; in, Component A includes by weight: Component B includes by weight: Curing agent 10-20 parts 40 to 100 parts of the second solvent; Component C includes by weight: Catalyst 5-10 parts 15 to 30 parts of the third solvent; The dopamine-modified polysiloxane polymer is prepared by free radical copolymerization and aminolysis reaction in sequence, and the specific steps are as follows: (1) In an argon-protected reactor, unsaturated pentafluorophenol ester monomer, unsaturated MQ silicone resin, unsaturated acrylate monomer, chain transfer agent, initiator azobisisobutyronitrile, and solvent are added in sequence, and then the temperature is raised to 65-75° C. for reaction for 5-8 hours; (2) pouring the reaction product into 5° C. methanol and filtering it multiple times, and drying the filtered product under vacuum conditions to obtain a prepolymer; (3) Add the prepolymer into a reaction kettle protected by argon, then add the dried dimethylformamide, dopamine salt monomer, and triethylamine, and then stir and react for 20 to 26 hours at room temperature; (4) The product after the reaction was precipitated into an excess of 0.5 wt % aqueous hydrogen chloride solution, and the polymer was recovered by filtration, followed by precipitation purification using a large amount of deionized water, and finally the purified polymer was dried and collected under vacuum conditions.

2. The coating according to claim 1, characterized in that The unsaturated pentafluorophenol ester monomer is selected from one of pentafluorophenyl acrylate, pentafluorophenyl methacrylate, and 4-vinylphenyl pentafluorobenzoate; the unsaturated MQ type silicone resin is selected from methyl vinyl MQ type siloxane resin, and its M:Q value is ≥1.3:1, or the methyl vinyl MQ type silicone resin is liquid at 25°C; the unsaturated acrylate monomer is selected from one of butyl methacrylate, methacrylate laurate, and butyl acrylate; the chain transfer agent is a RAFT agent; the dopamine salt monomer is selected from one of 6-hydroxydopamine hydrochloride, dopamine hydrochloride, and 5-hydroxydopamine hydrochloride.

3. The coating according to claim 1, characterized in that The weight ratio of unsaturated pentafluorophenol ester monomer, unsaturated MQ type silicone resin, unsaturated acrylic ester monomer, chain transfer agent, initiator azobisisobutyronitrile and solvent is 2: (30-45): (5-10): (0.1-0.4): (0.5-1): (40-80).

4. The coating according to claim 1, characterized in that The weight ratio of the prepolymer, dimethylformamide, dopamine salt monomer and triethylamine is (30-50): (50-120): (3-5): (5-10).

5. The coating according to claim 1, characterized in that The hydroxyl-terminated polysiloxane resin is selected from α,ω-dihydroxy polydimethylsiloxane having a viscosity of 2800-10000 mPa·s at 25°C.

6. A method for preparing a coating as claimed in any one of claims 1 to 5, characterized in that: The specific steps include: (1) Adding a hydroxyl-terminated polysiloxane resin, a dopamine-modified polysiloxane polymer, an auxiliary agent, and 50% of the first solvent to a dispersing and stirring device in sequence, and then dispersing at 100 rpm for 20 min, then adding a pigment and a filler and 50% of the first solvent to the dispersing and stirring device, and continuing to disperse at the same speed for 20 min, i.e., preparing component A, and then sealing and storing; (2) using a dispersing and stirring device to disperse the curing agent and the second solvent at 50 rpm for 10 min, i.e., preparing component B, and then sealing and storing; (3) Using a dispersing and stirring device at 50 rpm, the catalyst and the third solvent are dispersed for 10 minutes to prepare component C, which is then sealed and stored.

7. The antifouling coating prepared by the coating according to any one of claims 1 to 5, characterized in that: Component A, component B and component C are mixed evenly, applied on the substrate, and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.

Citation Information

Patent Citations

  • Surface coating polymer, and preparation method and application thereof

    CN110054732A

  • Bionic high-adhesion organosilicone marine antifouling paint and preparation method thereof

    CN114605913A

  • Modified organosilicone marine antifouling paint and preparation method thereof

    CN115093789A

  • Polymeric material and preparation method thereof

    CN115651123A

  • Functionalized modified fouling release type marine antifouling paint

    CN118813135A